Determination of Bolton Norms for Indian Population Sample (Orthodontic Journal of Nepal, 2017)
Introduction: Tooth size discrepancy varies between different ethnic groups and races. Bolton’s tooth size norms were originally determined in Caucasian population.Objective: To determine tooth size ratios for maxillary and mandibular dentition in Telangana population of Indian sample and to compare the ratios with standard Bolton norms.Materials & Method: The study sample comprised of 300 subjects (150 males and 150 females) aged between 14-25 years having Angle’s Class 1 molar relationship. Study models of all subjects were prepared and mesiodistal dimensions were measured to determine mean Bolton’s anterior ratio, overall ratio, over jet and overbite.Result: Evidence of sexual dimorphism was observed with Indian male subjects having greater mean values than the females. The determined mean for anterior tooth ratio was 80.88 ± 3.03%, overall tooth ratio 93.99 ± 3.11%, overjet 2.92 ± 0.62mm and overbite 2.96 ± 0.63mm. Statistically significant differences were found between Indian samples and Bolton Caucasian standards.Conclusion: The study provides evidence that tooth sizes are population specific. Mean values specific to particular population groups should be derived in order to make treatment planning more accurate and predictable.